STRATEGIES FOR THE FORMATION OF VOCAL HEARING AS WELL AS THE DEVELOPMENT OF VOCAL SKILLS - Nosirov Dilmurod Tursinovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This article will talk about the strategy for the formation of vocal hearing in educational institutions, as well as the development of vocal skills.